2021
DOI: 10.1109/jstqe.2019.2958999
|View full text |Cite
|
Sign up to set email alerts
|

InP-Based Grating Antennas for High-Resolution Optical Beam Steering

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…As the number of cascaded-layer increases, the divergence angle could be further reduced, depending on the advancement of the lithium niobate poled process. Compared with other high-resolution OPA [31][32][33][34][35] , the present cascaded-PPLN OPA shows great superiority in terms of the number of phase tuning units.…”
Section: A Principle Of Cascaded-ppln Opa and Simulationmentioning
confidence: 95%
“…As the number of cascaded-layer increases, the divergence angle could be further reduced, depending on the advancement of the lithium niobate poled process. Compared with other high-resolution OPA [31][32][33][34][35] , the present cascaded-PPLN OPA shows great superiority in terms of the number of phase tuning units.…”
Section: A Principle Of Cascaded-ppln Opa and Simulationmentioning
confidence: 95%
“…As seen in Fig. 2(b), the membrane-based BBs including the SOA [34]- [36], the isolator [48], the grating antenna [41] and the microheater share the same i-InP passive waveguide and n-InP layer including the same InGaAsP Q1.25 etch-stop. In Fig.…”
Section: A Conceptmentioning
confidence: 99%
“…This combination will empower dense monolithic circuits. For instance, densely integrated optical phased arrays can be produced by combining InP-membrane-based tunable lasers [35], semiconductor optical amplifiers (SOA) [34]- [36], [38], grating antennas [41], and microheaters monolithically on the same chip.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wang et al have demonstrated a grating antenna BB for beam steering on the IMOS platform [172], which exhibited a beam width of 0.05 • , setting a record for InPbased beam steerers. The antenna features a fabrication insensitive design and utilizes the double-sided processing for performance boost.…”
Section: Optical Wireless Communication (Owc)mentioning
confidence: 99%